2016
DOI: 10.1017/s0952523815000310
|View full text |Cite
|
Sign up to set email alerts
|

Multi-nucleate retinal pigment epithelium cells of the human macula exhibit a characteristic and highly specific distribution

Abstract: Background The human retinal pigment epithelium (RPE) is reportedly 3% bi-nucleated. The importance to human vision of multi-nucleated (MN)-RPE cells could be clarified with more data about their distribution in central retina. Methods Nineteen human RPE-flatmounts (9≤51years, 10>80 years) were imaged at 12 locations: 3 eccentricities (fovea, perifovea, near periphery) in 4 quadrants (superior, inferior, temporal, nasal). Image stacks of lipofuscin-attributable autofluorescence and phalloidin labeled F-actin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 36 publications
3
43
0
1
Order By: Relevance
“…In our in vivo study, we show that after LED exposure, a disorganization of the actin cytoskeleton and a disruption of tight junctions with an infiltration of albumin in the outer retina, indicating a permeabilization of the outer BRB, a feature seen in common retinopathies (diabetic retinopathy, for instance) 29. Moreover, we found early formations of polynucleated cells and an increase of the cells size both features related to ageing of the RPE cells 44, 45.…”
Section: Discussionsupporting
confidence: 56%
“…In our in vivo study, we show that after LED exposure, a disorganization of the actin cytoskeleton and a disruption of tight junctions with an infiltration of albumin in the outer retina, indicating a permeabilization of the outer BRB, a feature seen in common retinopathies (diabetic retinopathy, for instance) 29. Moreover, we found early formations of polynucleated cells and an increase of the cells size both features related to ageing of the RPE cells 44, 45.…”
Section: Discussionsupporting
confidence: 56%
“…We observed solitary cells as punctate reflective foci and swarms of multiple intraretinal RPE as large irregular foci. Although most swarms comprised groups of cells, we did also note some large individual cells that were multinucleate 29,30 (Figure 5). Experimental studies in mouse demonstrated that multinucleate RPE cells in the setting of a disintegrin-like and metalloproteinase with thrombospondin type 1 motif-like 4-deficiency can be migratory 37 , suggestive of a final common pathway to different stresses, while others indicate that failed cytokinesis in cell division can cause RPE multinucleation.…”
Section: Discussionmentioning
confidence: 82%
“…Figures 3D–E show single pigmented ‘intraretinal’ RPE cells in the outer nuclear and ganglion cell layers, respectively. Groups of intraretinal RPE in the Henle fiber layer, including several multinucleate cells 29,30 appeared to swarm (Figure 3F). Five RPE cells were seen to form a ring around an inner retinal capillary (Figure 3G).…”
Section: Resultsmentioning
confidence: 98%
“…In the aging parafovea, the region of high rod density, the RPE are hexagonal, enlarged, and have the highest frequency of multinucleated cells (Starnes et al, 2016). Of the possible causes of multinucleation, such as endoreplication, cell fusion, or incomplete cell division, Chen et al found that oxidative stress generated during the phagocytosis of oxidized outer segments, induces RPE proliferation, but cytokinesis failure, indicating that incomplete cell division is likely the primary etiology for multinucleation (Ach et al, 2014; Chen et al, 2016).…”
Section: Histopathologic Changes In Non-neovascular Amdmentioning
confidence: 99%
“…In early AMD, the RPE degenerates and assumes a mesenchymal morphology while photoreceptors can appear intact (Ach et al, 2015; Hartmann et al, 2011; Iwama et al, 2010; Sulzbacher et al, 2012; Vogt et al, 2011; Wu et al, 2014). With progressive RPE changes, parafoveal rods die before either the RPE or cones (Starnes et al, 2016), and surviving rods often lack outer segments (Curcio et al, 1996; Curcio et al, 1993). The RPE undergoes progressive degeneration as AMD advances with the most severe changes in GA (Ach et al, 2015; Vogt et al, 2011).…”
Section: Histopathologic Changes In Non-neovascular Amdmentioning
confidence: 99%